THE ADMINISTRATION STRATEGIES IMPROVING THE QUALITY OF EDUCATION OF SMALL SCHOOLS IN THE NORTHEAST REGION - Bangwiset, Suchart; Prommuangkhum, Sukhum; Nuntee, Sakdinaporn; Sanenpao, Kanon (Journal of Srilanchang Review, 2025)
The research on the objectives: 1) to study the current conditions, desired conditions, and needs of educational administration to develop the quality of education; 2) to create and develop educational administration strategies to develop the quality of education; and 3) to evaluate the strategy for developing educational administration to develop the quality of education. The research methodology is divided into 3 phases: Phase 1: to study the current conditions, desired conditions, and needs. The sample group consists of 364 administrators and 364 teachers, totaling 728 people. The research instrument is a questionnaire with a 5-level rating scale. Phase 2: to create and develop strategies, consisting of 2 steps: Phase 1: a multi-case study. The target group is 3 school administrators. The instrument used is a structured interview. Phase 2: group discussions by 9 qualified persons. The instrument used is a group discussion record. Phase 3: to experiment with the strategy. The target group is 2 schools. The instrument used is an assessment form and a behavioral observation form. Phase 4: to evaluate the strategy. The evaluation was based on 5 experts. The tools used were an evaluation form. Statistics used for quantitative data analysis were percentage, mean, standard deviation, index of priority of needs, and qualitative data analysis using content analysis. 1.The current state of practice regarding educational administration to develop the quality of education is at a moderate level. The desired condition overall is at the highest level. And the index of priority of necessity when considering each aspect, arranged from highest to lowest, the first 3 ranks are: 1) the aspect of creating a cooperation network to develop quality, 2) the aspect of creating satisfaction of service recipients, 3) the aspect of evaluating work performance. Strategies for developing educational administration to develop the quality of education in small schools consist of 5 strategic components and 5 educational administration components: 1) determining organizational objectives, 2) implementing an organizational structure that focuses on efficiency, 3) creating a network of cooperation to develop quality, 4) creating satisfaction among service recipients, and 5) evaluating work performance. Evaluation of the strategy for developing educational administration to consider the quality of education in small schools in terms of appropriateness, feasibility, usefulness, and correctness. Overall, it is at a high level in all aspects.